Problem of the definition and history of the study of Ukrainian euphony - Yarmolinska , Maryna (Current issues of Ukrainian linguistics: theory and practice, 2017)
The article deals with the concept of euphony, euphony definition / euphony in stylistiс. Special attention is paid to the differentiation of concepts and terms the euphony of language and euphony of speech. Such differentiation can have significant methodological meaning, stressing the opposition of paradymatics and syntagmatics. Special attention is paid to the ideas of the Ukrainian linguists about euphony. The article also maintains the notion of euphony elaborated not only by Ukrainian scientists (such as V. Blyznyuk, V. Vashchenko, I. Hanych, S. Dyachuk, I. Ohiyenko, H. Pashkovska, O. Peshkovskii, M. Pylynskyy, P. Tymoshenko, N. Tocka, V. Shyprykevych) but also by Ukrainian writers (for instance, I. Nechuy-Levytskyi). It gives the reader more than century-long history ofUkrainian euphony-studies. As it is shown in this article, euphony is one of the main feature of the Ukrainian language and can be regarded as a key-concept for the self-representation of Ukrainian nation.
Keywords: euphony, phonetic parameters, universaland ethnically specific factors, the transparency of language.